CORPORATE REBRANDING OF GRAMEDIA STORE (CORPORATE REBRANDING DI GRAMEDIA STORE) - Kairupan, Natasha Helena; Dida, Susanne; Budiana, Heru Ryanto (Prodi Teknologi Pendidikan, 2016)
Abstract. The purposes of this research are to determine the stages of analysis, planning, and evaluation of corporate rebranding process of Gramedia Book Store to be Gramedia Store to rise stakeholder’s awareness. The method used is descriptive qualitative with positivism paradigm. The technique of collecting data through in-depth interview, observation, and literature study. The result of this research showed the analysis stage by analyzing the market through insights and foresights, brand audit through SWOT analysis, and identifying opportunities. The planning stage is by determine the purpose of the planning process and then determine the target audience, consist of external and internal customer. The planning of external customer by renaming and change of corporate identity, and marketing planning using communication channel (above the line and below the line). The planning of internal customer by Brand Induction, training, inspiration briefing at store, and innovation competition. The evaluation of rebranding process of Gramedia Store is having a focus group discussion with customer, media monitoring, and presentation to BOD.Keywords : Process, Corporate Rebranding, Stakeholder Awareness, Corporate Identity, Gramedia StoreAbstrak.Tujuan penelitian ini adalah untuk mengetahui bagaimana tahapan analisis, perencanaan, dan evaluasi proses corporate rebranding Gramedia Book Store menjadi Gramedia Store untuk meningkatkan stakeholder awareness. Pendekatan yang digunakan adalah kualitatif dengan paradigma positivisme dan jenis studi deksriptif. Teknik pengumpulan data yang dilakukan melalui wawancara mendalam, observasi, dan studi pustaka. Berdasarkan hasil penelitian, tahapan analisis dilakukan dengan menganalisis pasar melalui insights dan foresights, audit merek dengan analisis SWOT, dan mengidentifikasi peluang. Dalam tahapan perencanaan dengan menentukan tujuan kemudian menentukan target audiens, yaitu eksternal dan internal. Perencanaan kepada external customer dilakukan dengan perubahan nama dan identitas perusahaan, melakukan perencanaan publikasi dan pemasaran menggunakan saluran komunikasi baik above the line dan below the line. Perencanaan kepada internal customer dilakukan dengan mengadakan brand induction, training, briefing inspirasi, dan lomba inovasi. Evaluasi dalam proses rebranding Gramedia Store dilakukan dengan focus group discussion dengan customer, media monitoring, dan presentasi ke BOD.Kata kunci : Proses, Corporate Rebranding, Stakeholder Awareness, Identitas Perusahaan, Gramedia Store